A low-resistance tin oxide-based target material and preparation method thereof

By doping specific ions in the tin oxide-based target and combining the sintering characteristics of SnO2, the problem of high resistivity of the tin oxide-based target is solved, and the effects of reducing resistivity, improving density and improving tissue uniformity are achieved.

CN118724584BActive Publication Date: 2025-04-25SHENZHEN APG MATERIAL TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411072768.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2025-04-25
Estimated Expiration
2044-08-06

AI Technical Summary

Technical Problem

The existing tin oxide-based targets have a high resistivity problem, which makes it difficult to form high-density and uniformly structured targets.

Method used

By doping Sb5+, Nb5+, Ta5+, Mo6+ or W6+ plasmas in SnO2, free electron carriers are introduced to reduce the resistivity, and by doping Zn2+, Cu2+, Bi3+, and B3+ plasmas, densification and sintering of SnO2 is promoted. Combined with the advantages of both, the density and tissue uniformity of the tin oxide-based target material are improved.

Benefits of technology

The resistivity reduction, density improvement and tissue uniformity improvement of tin oxide-based targets are achieved, and the advantages of low resistance, high density and uniform tissue are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724584B_ABST
    Figure CN118724584B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of target material preparation, and provides a low-resistance tin oxide-based target material and a preparation method thereof. The tin oxide-based target material comprises SnO2, a first dopant and a second dopant, wherein the first dopant comprises at least one of Sb2O5, Nb2O5, Ta2O5, MoO3 and WO3; and the second dopant comprises at least one of ZnO, CuO, Bi2O3 and B2O3. The low-resistance tin oxide-based target material provided by the present application uses SnO2 as the main material, and a certain amount of Sb is doped by the first dopant. 5+ , Nb 5+ 、 5+ 、Mo 6+ or W 6+ These ions enter the SnO2 lattice and replace Sn 4+ , which will introduce free electron carriers and increase the electron carrier concentration, thereby reducing the resistivity of the target material; the second dopant promotes the densification sintering of SnO2, so the formed tin oxide-based target has the characteristics of low resistance and high density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of target material preparation, and in particular relates to a low-resistance tin oxide-based target material and a preparation method thereof. Background Art

[0002] Transparent conductive oxide (TCO) films are widely used in display screens, solar cells and other fields due to their unique properties. Traditional indium oxide-based films, especially tin-doped indium oxide (ITO) films, occupy an important position in these fields due to their high light transmittance, excellent conductivity and stability. However, indium is a rare metal with limited and uneven resource reserves. With the growth of global demand for indium, its price continues to rise, which greatly increases the cost of ITO films. This limits the widespread application of ITO films to a certain extent, especially in the field of large-scale production. In contrast, tin oxide raw materials have a wide range of sources, abundant reserves and relatively low prices. In addition, tin oxide-based films have high light transmittance, excellent conductivity and good chemical stability. Therefore, in this context, tin oxide-based films show great application potential due to their unique advantages and are expected to become a substitute for ITO films.

[0003] At present, the preparation process of tin oxide-based targets is usually to combine various doping materials and SnO 2 The main materials are ball-milled and mixed evenly, and then granulated, molded and sintered. 2 The sintering properties are poor and it is difficult to sinter densely at high temperatures. 2 When the main materials are sintered together, it is easy to form a variety of intermediate compounds and segregation phases, and the target material has poor uniformity of organization, resulting in a higher resistivity of the tin oxide-based target material and difficulty in forming a high-density target material.

[0004] Therefore, the existing tin oxide-based target materials and preparation methods thereof still need to be improved. Summary of the invention

[0005] The purpose of the present application is to provide a low-resistance tin oxide-based target material and a preparation method thereof, in order to solve the problem of high resistivity of existing tin oxide-based target materials.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present invention provides a tin oxide-based target material, comprising SnO 2 , a first dopant and a second dopant, wherein the first dopant comprises Sb 2 O 5 , Nb 2 O 5 、 2 O 5 、MoO3 and WO 3 At least one of the following: The second dopant includes ZnO, CuO, Bi 2 O 3 and B 2 O 3 At least one of .

[0008] In a second aspect, the present application provides a method for preparing the low-resistance tin oxide-based target material described above, comprising the following steps:

[0009] The first dopant, tin oxide powder, the first dispersant and the solvent are ball-milled and mixed under a grinding medium, and then dried to obtain a first mixed powder;

[0010] calcining the first mixed powder to obtain a solid solution powder;

[0011] The solid solution powder is mixed with the second dopant, the second dispersant, the binder and the solvent by ball milling, and then dried to obtain a second mixed powder;

[0012] isostatically pressing the second mixed powder to form a green billet;

[0013] The green blank is sintered to obtain a tin oxide-based target.

[0014] Compared with the prior art, this application has the following beneficial effects:

[0015] In the first aspect, the low-resistance tin oxide-based target provided by the present application is SnO 2 As the main material, a certain amount of Sb is doped by the first dopant 5+ , Nb 5+ 、 5+ 、Mo 6+ or W 6+ These ions enter SnO 2 Substituting Sn in the lattice 4+ , will introduce free electron carriers, increase the electron carrier concentration, and thus greatly reduce the resistivity of the tin oxide-based target material. However, these ions will inhibit the bonding of grains to a certain extent, reducing the SnO 2 Sintering characteristics of Zn by doping with a second dopant 2+ , Cu 2+ 、Bi 3+ , B 3+ These ions can promote SnO by generating oxygen vacancies or generating liquid phase. 2 However, these ions will produce grain boundary barriers in the grain boundary area, reduce the mobility of carriers, and increase the resistivity to a certain extent. Therefore, SnO 2Under the synergistic effect of the first dopant and the second dopant, the disadvantages of the first dopant and the second dopant can be overcome, and the advantages of the two can be combined to improve the density and organizational uniformity of the tin oxide-based target material and reduce the resistivity. Therefore, the tin oxide-based target material of the present application has the advantages of low resistance, high density and uniform organization.

[0016] The second aspect of the present application provides a method for preparing a low-resistance tin oxide-based target material, first calcining the first dopant and tin oxide powder, so that the first dopant is dissolved in the lattice of tin oxide to form a solid solution powder, and then mixed with the second dopant for molding and sintering, so that the second dopant can fully play the role of promoting the sintering of tin oxide powder, so that it is easier to form a uniform and dense tin oxide-based target material, reduce the resistivity, and avoid directly sintering the first dopant, the second dopant and the tin oxide powder together to generate a variety of intermediate compounds and segregation phases. In addition, in the cooling stage of the sintering treatment, an argon-hydrogen mixed gas is introduced to form a reducing atmosphere, which can not only deoxygenate the target material and reduce the resistivity of the target material, but also promote the uniformity of the internal structure of the target material and improve the density, thereby reducing the obstacles of the voids and defects inside the material to the resistance transmission, making the electron transmission smoother, and further reducing the resistivity of the target material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope of the present invention.

[0018] Figure 1 This is a cross-sectional microscopic morphology of the tin oxide-based target material of Example 1 of the present invention. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0020] The first aspect of the embodiment of the present application provides a low-resistance tin oxide-based target material, comprising SnO 2 , a first dopant and a second dopant, the first dopant comprising Sb 2 O 5 , Nb 2 O 5 、 2 O 5 、MoO 3 and WO 3 At least one of the following: The second dopant includes ZnO, CuO, Bi 2 O 3and B 2 O 3 At least one of .

[0021] It should be noted that SnO 2 , the first dopant and the second dopant may refer to raw materials for preparing a low-resistance tin oxide-based target material.

[0022] In the embodiment, Sb 2 O 5 , Nb 2 O 5 、 2 O 5 、MoO 3 , WO 3 、ZnO、CuO、Bi 2 O 3 and B 2 O 3 The purity of the raw material powder is greater than or equal to 99.99%, and the content of Ca, Fe, Si, and Mn is less than 20ppm, and the total impurity content is less than 100ppm. By controlling the purity of the raw materials, it is possible to greatly reduce the impurities remaining in the film during target coating to form magnetic impurities and affect the optical and electrical properties of the coating, thereby obtaining better photoelectric properties.

[0023] The low-resistance tin oxide-based target material provided in the embodiment of the present application is SnO 2 As the main material, a certain amount of Sb is doped by the first dopant 5+ , Nb 5+ 、 5+ 、Mo 6+ or W 6+ These ions enter SnO 2 Substituting Sn in the lattice 4+ , will introduce free electron carriers, increase the electron carrier concentration, and thus greatly reduce the resistivity of the tin oxide-based target material. However, these ions will inhibit the bonding of grains to a certain extent, reducing the SnO 2 Sintering characteristics of Zn by doping with a second dopant 2+ , Cu 2+ 、Bi 3+ , B 3 + These ions can promote SnO by generating oxygen vacancies or generating liquid phase. 2 However, these ions will produce grain boundary barriers in the grain boundary area, reduce the mobility of carriers, and increase the resistivity to a certain extent. Therefore, SnO 2Under the synergistic effect of the first dopant and the second dopant, the disadvantages of the first dopant and the second dopant can be overcome, and the advantages of the two can be combined to improve the density and organizational uniformity of the tin oxide-based target material and reduce the resistivity. Therefore, the tin oxide-based target material of the present application has the advantages of low resistance, high density and uniform organization.

[0024] In the embodiment, SnO 2 , the mass ratio of the first dopant to the second dopant is (94-99.8) / (0.1-3) / (0.1-3), preferably (96-98) / (1-2) / (1-2), specifically 94 / 3 / 3, 95 / 2 / 3, 96 / 2 / 2, 97 / 2 / 1, 98 / 1 / 1, 99 / 0.5 / 0.5, 99.8 / 0.1 / 0.1, etc. As long as SnO 2 The mass ratio of the first dopant to the second dopant can be in the range of (94-99.8) / (0.1-3) / (0.1-3). Adding an appropriate amount of the first dopant helps to reduce the resistivity of the target material, and adding an appropriate amount of the second dopant helps to improve the SnO 2 However, if the addition amount of the first dopant and the second dopant is too low, it is not conducive to reducing the resistivity of the target material, and the improvement of the sintering characteristics of tin dioxide is not obvious. The structure uniformity and density of the formed target material are not high, and the resistivity is large; if the addition amount of the first dopant and the second dopant is too high, the first dopant will inhibit the combination of the grains to a certain extent, reducing the SnO 2 The sintering characteristics of the target material are not conducive to improving the organizational uniformity and density of the target material. The second dopant will produce more grain boundary barriers in the grain boundary area, reduce the carrier mobility, and reduce the resistivity to a certain extent. The organizational uniformity and density of the target material formed are not high, and the resistivity is also large. Therefore, the addition amount of the first dopant and the second dopant within the range of this embodiment can significantly improve the sintering characteristics of tin dioxide, improve the density and organizational uniformity of the tin oxide-based target material, and reduce the resistivity of the target material.

[0025] In the embodiment, the resistivity of the tin oxide-based target is ≤50 mΩ·cm, and the density is >6.5 g / cm 3 Therefore, the tin oxide-based target material of this embodiment has the advantages of high density and low resistivity.

[0026] A second aspect of an embodiment of the present application provides a method for preparing a low-resistance tin oxide-based target material, comprising the following steps:

[0027] S1: The first dopant, tin oxide powder (SnO 2 powder), a first dispersant and a solvent are ball-milled and mixed under a grinding medium, and then dried to obtain a first mixed powder;

[0028] S2: calcining the first mixed powder to obtain a solid solution powder;

[0029] S3: ball-milling the solid solution powder, the second dopant, the second dispersant, the binder and the solvent, and then drying to obtain a second mixed powder;

[0030] S4: isostatically pressing the second mixed powder to form a green billet;

[0031] S5: Sintering the green blank to obtain a tin oxide-based target.

[0032] Due to Sb 2 O 3 The sintering characteristics are poor. If the first dopant, the second dopant and SnO are directly 2 After ball milling and mixing, granulation and molding are easy to form a variety of intermediate compounds in subsequent sintering, segregation phases are equal, the target material has poor uniformity, and it is difficult to form a high-density and low-resistance target material. The preparation method of the low-resistance tin oxide-based target material provided in the embodiment of the present application is to first calcine the first dopant with the tin oxide powder, so that the first dopant is dissolved in the lattice of the tin oxide to form a solid solution powder, and then mixed with the second dopant for molding and sintering, so that the second dopant can fully play the role of promoting the sintering of the tin oxide powder, so that it is easier to form a uniform and dense tin oxide-based target material, reduce the resistivity, and avoid directly sintering the first dopant, the second dopant and the tin oxide powder together to generate a variety of intermediate compounds and segregation phases. In addition, in the cooling stage of the sintering treatment, an argon-hydrogen mixed gas is introduced to form a reducing atmosphere, which can not only deoxygenate the target material and reduce the resistivity of the target material, but also promote the uniformity of the internal structure of the target material and improve the density, thereby reducing the obstacles of the voids and defects inside the material to the resistance transmission, making the electron transmission smoother, and thus further reducing the resistivity of the target material.

[0033] In the above step S1 , the specific material and content of the first dopant are as described above, and will not be repeated here to save space.

[0034] In the embodiment, the mass ratio of the first dopant to the grinding medium is 1 / (1-3); the grinding medium includes a first zirconia bead, a second zirconia bead, a third zirconia bead and a fourth zirconia bead in a mass ratio of 1 / (2-4) / (2-4) / (4-8); wherein the particle sizes of the first zirconia bead, the second zirconia bead, the third zirconia bead and the fourth zirconia bead are 0.5-3 mm, 4-6 mm, 8-12 mm and 13-16 mm, respectively. Specifically, the mass ratio of the first zirconia bead, the second zirconia bead, the third zirconia bead and the fourth zirconia bead can be 1 / 2 / 2 / 4, 1 / 3 / 3 / 5, 1 / 3 / 4 / 6, 1 / 3 / 3 / 8, 1 / 4 / 3 / 5 or 1 / 4 / 3 / 8, etc., as long as the mass ratio of the four is within the range of 1 / (2-4) / (2-4) / (4-8); the particle size of the first zirconia bead It can be 0.5mm, 0.8mm, 1.0mm, 1.3mm, 1.5mm, 2.0mm, 2.5mm or 3.0mm, as long as the particle size of the first zirconia beads is within the range of 0.5-3mm; the particle size of the second zirconia beads can be 4mm, 4.5mm, 5.0mm, 5.5mm or 6.0mm, as long as the particle size of the second zirconia beads is within the range of 4-6mm; the particle size of the third zirconia beads can be 8mm, 8.5mm, 9.0mm, 10mm, 11mm or 12mm, as long as the particle size of the third zirconia beads is within the range of 8-12mm; the particle size of the fourth zirconia beads can be 13mm, 13.5mm, 14.0mm, 14.5mm, 15mm or 16mm, as long as the particle size of the fourth zirconia beads is within the range of 13-16mm. Controlling the zirconia beads of each particle size range within the specific mass ratio range of the present embodiment is conducive to the formation of finer powders, more uniform powder mixing, and smaller gaps between powder particles, so that the mixed powder has higher sintering activity and is easier to sinter to form a solid solution powder with uniform structure. In addition, it can also avoid the damage to the powder morphology during the ball milling mixing process and the large difference in the grain size of the obtained mixed powder.

[0035] In an embodiment, the grinding media may consist of first zirconia beads, second zirconia beads, third zirconia beads, and fourth zirconia beads.

[0036] In an embodiment, the first dispersant is selected from ammonium polyacrylate, the solvent is selected from deionized water, and the added amount of the first dispersant is 0.01-0.1% of the total mass of the first dopant and tin oxide powder, for example 0.1%, 0.02%, 0.05%, 0.07%, 0.08%, 0.09% or 0.1%, etc.

[0037] In the above step S2, the step of calcining the first mixed powder includes: heating the first mixed powder to 750-850°C, keeping it warm for 4-12 hours, then cooling it to 450-550°C, keeping it warm for 6-10 hours, and then cooling it with the furnace. Such calcination treatment is conducive to the first dopant being dissolved into the tin oxide lattice to form a solid solution powder, while preventing the decomposition or segregation of the components, reducing the formation of intermediate compounds, segregation phases, etc., and improving the uniformity of the target material structure, thereby reducing resistance and increasing density. If the calcination temperature of the first mixed powder is too low, it is difficult to form a solid solution powder with a uniform structure. If the calcination temperature is too high, it is easy to cause the volatile components to volatilize, or segregation, etc., which will ultimately affect the uniformity of the target material structure.

[0038] In the embodiment, the specific surface area of ​​the solid solution powder is 3 to 8 m 2 / g, for example 3m 2 / g, 4m 2 / g, 5m 2 / g、m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, etc.; the specific surface area of ​​the second mixed powder is 8 to 15m 2 / g, for example 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 The first dopant, tin oxide powder, the first dispersant and the solvent are ball-milled under a grinding medium, dried and then calcined, and the solid solution powder is crushed to have a specific surface area of ​​3 to 8 m 2 / g, which is conducive to more uniform mixing with the second dopant by ball milling, and forms a specific surface area of ​​8 to 15m 2 / g of the second mixed powder makes the gaps between powder particles smaller and the sintering activity higher, thereby making the target material denser, with better structural uniformity and lower resistance.

[0039] In the above step S3, the specific material and content of the second dopant are as described above, and will not be repeated here to save space.

[0040] In an embodiment, the step of ball-milling the solid solution powder with the second dopant, the second dispersant, the binder and the solvent, and then drying to obtain the second mixed powder may include: ball-milling the solid solution powder, the second dopant, the second dispersant and the solvent, then adding the binder and mixing evenly, filtering and drying at 80°C to obtain the second mixed powder.

[0041] In an embodiment, the second dispersant is selected from ammonium polycarboxylate, the binder is selected from polyvinyl alcohol, the solvent is selected from water, and the added amount of the second dispersant is 0.01 to 0.1% of the total mass of the solid solution powder and the second dopant, for example 0.1%, 0.02%, 0.05%, 0.07%, 0.08%, 0.09% or 0.1%, etc.

[0042] In the above step S4, the isostatic pressing pressure is 200-300 MPa, and can further be 200-220 MPa, 220-240 MPa, 240-260 MPa, 260-280 MPa or 280-300 MPa.

[0043] In the above step S5, the step of sintering the green blank includes: placing the green blank in a sintering furnace, heating it to 400-600°C at a heating rate of 5-10°C / min under an air atmosphere, keeping it warm for 18-60 hours, heating it to 600-800°C at a heating rate of 1-3°C / min, keeping it warm for 4-6 hours, heating it to 800-1400°C at a heating rate of 5-10°C / min, keeping it warm for 12-18 hours, heating it to 1400-1550°C at a heating rate of 1-3°C / min, keeping it warm for 12-24 hours, cooling it to 800-1200°C, introducing argon-hydrogen mixed gas, keeping it warm for 2-6 hours, cooling it to 700°C, stopping the introduction of gas, and cooling it naturally.

[0044] Specifically, in an air atmosphere, the temperature is raised to 400-600°C at a heating rate of 5-10°C / min and kept for 18-60 hours. In this stage, organic substances such as dispersants and binders can be removed to improve the purity of the target material; then the temperature is raised to 600-800°C at a heating rate of 1-3°C / min and kept for 4-6 hours. In this stage, the green body can be fully vented and the powder particles can be homogenized, thereby promoting sintering densification; then the temperature is raised to 800-1400°C at a heating rate of 5-10°C / min and kept for 12-18 hours. In this stage, the particles can be more closely bonded, the gaps gradually disappear, and the density of the target material is improved; then the temperature is raised to 1400-1550°C at a heating rate of 1-3°C / min and kept for 12-18 hours. 12 to 24 hours, in this stage, the temperature is further increased to promote grain growth, improve target uniformity, and reduce resistance; finally, the temperature is lowered to 800 to 1200°C, and an argon-hydrogen mixed gas is introduced. After keeping the temperature for 2 to 6 hours, the temperature is lowered to 700°C, and the gas introduction is stopped, and the temperature is naturally lowered. During the cooling stage, an argon-hydrogen mixed gas is introduced to form a reducing atmosphere, which can not only deoxygenate the target and reduce the resistivity of the target, but also promote the uniformity of the internal structure of the target and improve the density, reduce the obstacles of the voids and defects inside the material to the resistance transmission, make the electron transmission smoother, and further reduce the resistivity of the target; therefore, through the sintering treatment of this embodiment, the tin oxide target has the advantages of high density, good uniformity of organization and low resistivity.

[0045] The following describes the invention in conjunction with specific embodiments.

[0046] Example 1

[0047] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof.

[0048] Low-resistance tin oxide-based target, the raw materials include SnO with a mass ratio of 97 / 1.5 / 1.5 2 , a first dopant and a second dopant, wherein the first dopant is selected from Sb 2 O 5 , the second dopant is ZnO.

[0049] A method for preparing a low-resistance tin oxide-based target material comprises the following steps:

[0050] S11: According to the specific raw material composition and proportion of the tin oxide-based target material of this embodiment, weigh an appropriate amount of SnO with a purity greater than or equal to 99.99%, a Ca, Fe, Si, and Mn content less than 20 ppm, and a total impurity content less than 100 ppm. 2 Powder, Sb 2 O 5 powder and ZnO powder;

[0051] S12: Sb 2 O 5Powder, SnO 2 The powder, ammonium polyacrylate and water are ball-milled under a grinding medium, and then filtered and dried to obtain a first mixed powder; wherein the amount of ammonium polyacrylate added is Sb 2 O 5 Powder and SnO 2 0.05% of the total mass of powder, Sb 2 O 5 Powder and SnO 2 The mass ratio of the total mass of the powder to the mass ratio of the grinding medium is 1 / 2, and the grinding medium is composed of a first zirconia bead (2 mm), a second zirconia bead (5 mm), a third zirconia bead (10 mm), and a fourth zirconia bead (15 mm) in a mass ratio of 1 / 3 / 3 / 6;

[0052] S13: The first mixed powder is placed in a calcining furnace, first heated to 800°C and kept at this temperature for 8 hours, then cooled to 500°C and kept at this temperature for 8 hours, and then cooled with the calcining furnace, and crushed to obtain a specific surface area of ​​5m 2 / g of solid solution powder;

[0053] S14: The solid solution powder, ZnO powder, ammonium polycarboxylate and water were ball-milled and mixed, and then polyvinyl alcohol was added and mixed evenly, and then filtered and dried to obtain a specific surface area of ​​12m 2 / g of the second mixed powder; wherein the addition amount of ammonium polycarboxylate and polyvinyl alcohol is 0.05% of the total mass of the solid solution powder and the ZnO powder;

[0054] S15: the second mixed powder is loaded into a stainless steel mold, preformed by a hydraulic press, and then cold isostatically pressed at a pressure of 250 MPa to form a green blank;

[0055] S16: Place the green blank in a sintering furnace, and heat it to 500°C at a heating rate of 7°C / min in an air atmosphere. After keeping it warm for 36 hours, heat it to 700°C at a heating rate of 2°C / min. After keeping it warm for 5 hours, heat it to 1100°C at a heating rate of 7°C / min. After keeping it warm for 15 hours, heat it to 1500°C at a heating rate of 2°C / min. After keeping it warm for 18 hours, cool it to 1100°C, introduce argon-hydrogen mixed gas, keep it warm for 4 hours, cool it to 700°C, stop introducing gas, cool it naturally, and obtain a tin oxide-based target.

[0056] Example 2

[0057] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is that: SnO 2 , Sb 2 O 5 The mass ratio of Ag and ZnO is 94 / 3 / 3.

[0058] Example 3

[0059] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is that: SnO 2 , Sb 2 O 5 The mass ratio of Ag and ZnO is 99.8 / 0.1 / 0.1.

[0060] Example 4

[0061] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0062] The low-resistance tin oxide-based target material, the first dopant is selected from Sb with a mass ratio of 0.5 / 1 2 O 5 , Nb 2 O 5 .

[0063] A method for preparing a low-resistance tin oxide-based target material, in step S11, weighing an appropriate amount of SnO with a purity greater than or equal to 99.99%, a content of Ca, Fe, Si, and Mn less than 20 ppm, and a total impurity content less than 100 ppm 2 Powder, Sb 2 O 5 Powder, Nb 2 O 5 powder and ZnO powder; in step S12, Sb 2 O 5 Powder, Nb 2 O 5 Powder, SnO 2 The powder, ammonium polyacrylate and water are ball-milled under grinding media.

[0064] Example 5

[0065] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0066] A low-resistance tin oxide-based target material, wherein the first dopant is selected from Sb in a mass ratio of 0.5 / 0.5 / 0.5 2 O 5 , Nb 2 O 5 , WO 3 .

[0067] A method for preparing a low-resistance tin oxide-based target material, in step S11, weighing an appropriate amount of SnO with a purity greater than or equal to 99.99%, a content of Ca, Fe, Si, and Mn less than 20 ppm, and a total impurity content less than 100 ppm 2 Powder, Sb 2 O 5 Powder, Nb2 O 5 Pink, WO 3 powder and ZnO powder; in step S12, Sb 2 O 5 Powder, Nb 2 O 5 Pink, WO 3 Powder, SnO 2 The powder, ammonium polyacrylate and water are ball-milled under grinding media.

[0068] Example 6

[0069] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0070] A low-resistance tin oxide-based target material, wherein the first dopant is selected from Sb in a mass ratio of 0.5 / 0.5 / 0.5 2 O 5 , Nb 2 O 5 、MoO 3 .

[0071] A method for preparing a low-resistance tin oxide-based target material, in step S11, weighing an appropriate amount of SnO with a purity greater than or equal to 99.99%, a content of Ca, Fe, Si, and Mn less than 20 ppm, and a total impurity content less than 100 ppm 2 Powder, Sb 2 O 5 Powder, Nb 2 O 5 Powder, MoO 3 powder and ZnO powder; in step S12, Sb 2 O 5 Powder, Nb 2 O 5 Powder, MoO 3 Powder, SnO 2 The powder, ammonium polyacrylate and water are ball-milled under grinding media.

[0072] Example 7

[0073] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0074] Low resistance tin oxide based target, SnO 2 , the mass ratio of the first dopant and the second dopant is 96.5 / 2 / 1.5, and the first dopant is selected from Sb with a mass ratio of 0.5 / 0.5 / 0.5 / 0.5 2 O 5 , Nb 2 O 5 、MoO3 , WO 3 , the second dopant is selected from ZnO and CuO in a mass ratio of 1 / 0.5.

[0075] A method for preparing a low-resistance tin oxide-based target material, in step S11, weighing an appropriate amount of SnO with a purity greater than or equal to 99.99%, a content of Ca, Fe, Si, and Mn less than 20 ppm, and a total impurity content less than 100 ppm 2 Powder, Sb 2 O 5 Powder, Nb 2 O 5 Powder, MoO 3 Pink, WO 3 powder, ZnO powder and CuO powder; in step S12, Sb 2 O 5 Powder, Nb 2 O 5 Powder, MoO 3 Pink, WO 3 Powder, SnO 2 The powder, ammonium polyacrylate and water are ball-milled under grinding media.

[0076] Example 8

[0077] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0078] S13: The first mixed powder is placed in a calcining furnace, first heated to 750°C, kept at this temperature for 8 hours, then cooled to 450°C, kept at this temperature for 8 hours, and then cooled with the calcining furnace, and crushed to obtain a specific surface area of ​​8m 2 / g of solid solution powder.

[0079] Example 9

[0080] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0081] S13: Place the mixed powder in a calcining furnace, first heat it to 850°C, keep it warm for 8 hours, then cool it to 550°C, keep it warm for 8 hours, and then cool it with the calcining furnace and crush it to obtain a specific surface area of ​​3m 2 / g of solid solution powder.

[0082] Example 10

[0083] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0084] S16: Place the green blank in a sintering furnace, and heat it to 400°C at a heating rate of 5°C / min in an air atmosphere. After keeping it warm for 60 hours, heat it to 600°C at a heating rate of 1°C / min. After keeping it warm for 6 hours, heat it to 800°C at a heating rate of 5°C / min. After keeping it warm for 18 hours, heat it to 1400°C at a heating rate of 1°C / min. After keeping it warm for 24 hours, cool it down to 800°C, introduce argon-hydrogen mixed gas, and after keeping it warm for 6 hours, cool it down to 700°C. Stop introducing gas, cool it down naturally, and obtain a tin oxide-based target.

[0085] Embodiment 11

[0086] This embodiment provides a low-resistance tin oxide-based target material and a preparation method thereof. The difference from embodiment 1 is:

[0087] S16: Place the green blank in a sintering furnace, and heat it to 600°C at a heating rate of 10°C / min in an air atmosphere. After keeping it warm for 18 hours, heat it to 800°C at a heating rate of 3°C / min. After keeping it warm for 4 hours, heat it to 1400°C at a heating rate of 10°C / min. After keeping it warm for 12 hours, heat it to 1550°C at a heating rate of 3°C / min. After keeping it warm for 12 hours, cool it to 1200°C, introduce argon-hydrogen mixed gas, and after keeping it warm for 2 hours, cool it to 700°C. Stop introducing gas, cool it naturally, and obtain a tin oxide-based target.

[0088] Comparative Example 1

[0089] This comparative example provides a tin oxide target material and a preparation method thereof.

[0090] Tin oxide based target, the raw materials include SnO with a mass ratio of 97 / 1.5 / 1.5 2 , a first dopant and a second dopant, wherein the first dopant is selected from Sb 2 O 5 , the second dopant is ZnO.

[0091] A method for preparing a tin oxide-based target material comprises the following steps:

[0092] S1: According to the specific raw material components and proportions of the tin oxide-based target material of this comparative example, weigh an appropriate amount of SnO with a purity greater than or equal to 99.99%, a Ca, Fe, Si, and Mn content less than 20 ppm, and a total impurity content less than 100 ppm. 2 Powder, Sb 2 O 5 powder and ZnO powder;

[0093] S2: SnO 2 Powder, Sb 2 O 5Powder, ZnO powder, ammonium polyacrylate and water are ball-milled and mixed, and then polyvinyl alcohol is added and mixed evenly to obtain a mixed slurry with a solid content of 65%;

[0094] S3: introducing the mixed slurry into a granulator with an inlet temperature of 200°C and an outlet temperature of 90°C to obtain granulated powder;

[0095] S4: The granulated powder is loaded into a stainless steel mold, preformed by a hydraulic press, and then cold isostatically pressed at a pressure of 250 MPa to form a green blank;

[0096] S5: Place the green blank in a sintering furnace, and heat it to 500°C at a heating rate of 7°C / min under air atmosphere. After keeping it warm for 36 hours, heat it to 700°C at a heating rate of 2°C / min. After keeping it warm for 5 hours, heat it to 1100°C at a heating rate of 7°C / min. After keeping it warm for 15 hours, heat it to 1500°C at a heating rate of 2°C / min. After keeping it warm for 18 hours, cool it to 1100°C, introduce argon-hydrogen mixed gas, keep it warm for 4 hours, cool it to 700°C, stop introducing gas, and cool it naturally to obtain a tin oxide target.

[0097] Comparative Example 2

[0098] This comparative example provides a tin oxide-based target material and a preparation method thereof.

[0099] Tin oxide based targets, including SnO with a mass ratio of 97 / 3 2 and a first dopant, wherein the first dopant is selected from Sb 2 O 5 .

[0100] The method for preparing a tin oxide-based target material comprises the following steps:

[0101] S1: According to the specific raw material components and proportions of the tin oxide-based target material of this comparative example, weigh an appropriate amount of SnO with a purity greater than or equal to 99.99%, a Ca, Fe, Si, and Mn content less than 20 ppm, and a total impurity content less than 100 ppm. 2 Powder and Sb 2 O 5 pink;

[0102] S2: Sb 2 O 5 Powder, SnO 2 The powder, ammonium polyacrylate and water are ball-milled under a grinding medium, and then filtered and dried to obtain a first mixed powder; wherein the amount of ammonium polyacrylate added is Sb 2 O 5 Powder and SnO 2 0.05% of the total mass of powder, Sb 2 O 5 Powder and SnO2 The mass ratio of the total mass of the powder to the mass ratio of the grinding medium is 1 / 2, and the grinding medium is composed of a first zirconia bead (2 mm), a second zirconia bead (5 mm), a third zirconia bead (10 mm), and a fourth zirconia bead (15 mm) in a mass ratio of 1 / 3 / 3 / 6;

[0103] S3: The first mixed powder is placed in a calcining furnace, first heated to 800°C for 8 hours, then cooled to 500°C for 8 hours, and then cooled with the calcining furnace, and crushed to obtain a specific surface area of ​​5m 2 / g of solid solution powder;

[0104] S4: the solid solution powder is loaded into a stainless steel mold, preformed by a hydraulic press, and then cold isostatically pressed at a pressure of 250 MPa to form a green billet;

[0105] S5: Place the green blank in a sintering furnace, and heat it to 500°C at a heating rate of 7°C / min under air atmosphere. After keeping it warm for 36 hours, heat it to 700°C at a heating rate of 2°C / min. After keeping it warm for 5 hours, heat it to 1100°C at a heating rate of 7°C / min. After keeping it warm for 15 hours, heat it to 1500°C at a heating rate of 2°C / min. After keeping it warm for 18 hours, cool it to 1100°C, introduce argon-hydrogen mixed gas, keep it warm for 4 hours, cool it to 700°C, stop introducing gas, cool it naturally, and obtain a tin oxide-based target.

[0106] Comparative Example 3

[0107] This comparative example provides a tin oxide-based target material and a preparation method thereof.

[0108] Tin oxide based targets, including SnO with a mass ratio of 97 / 3 2 and a second dopant, wherein the second dopant is ZnO.

[0109] A method for preparing a tin oxide-based target material comprises the following steps:

[0110] S1: According to the specific raw material components and proportions of the tin oxide-based target material of this comparative example, weigh an appropriate amount of SnO with a purity greater than or equal to 99.99%, a Ca, Fe, Si, and Mn content less than 20 ppm, and a total impurity content less than 100 ppm. 2 powder and ZnO powder;

[0111] S2: SnO 2 The powder, ZnO powder, ammonium polycarboxylate and water were ball-milled and mixed, and then polyvinyl alcohol was added and mixed evenly, and then filtered and dried to obtain a specific surface area of ​​12m 2 / g mixed powder; wherein the addition amount of polycarboxylic acid ammonium and polyvinyl alcohol is SnO 2 0.05% of the total mass of powder and ZnO powder;

[0112] S3: The mixed powder is loaded into a stainless steel mold, preformed with a hydraulic press, and then cold isostatically pressed at a pressure of 250 MPa to form a green blank;

[0113] S4: Place the green blank in a sintering furnace, and heat it to 500°C at a heating rate of 7°C / min under air atmosphere. After keeping it warm for 36 hours, heat it to 700°C at a heating rate of 2°C / min. After keeping it warm for 5 hours, heat it to 1100°C at a heating rate of 7°C / min. After keeping it warm for 15 hours, heat it to 1500°C at a heating rate of 2°C / min. After keeping it warm for 18 hours, cool it to 1100°C, introduce argon-hydrogen mixed gas, keep it warm for 4 hours, cool it to 700°C, stop introducing gas, cool it naturally, and obtain a tin oxide-based target.

[0114] Comparative Example 4

[0115] This comparative example provides a tin oxide-based target material and a preparation method thereof. The difference from Example 1 is:

[0116] Step S13: Place the mixed powder in a calcining furnace, heat it to 800°C and keep it for 8 hours, then cool it to room temperature as the calcining furnace cools it, and crush it to obtain a powder with a specific surface area of ​​5m 2 / g of solid solution powder.

[0117] Comparative Example 5

[0118] This comparative example provides a tin oxide-based target material and a preparation method thereof. The difference from Example 1 is:

[0119] S16: Place the green billet in a sintering furnace, heat it to 500°C at a heating rate of 7°C / min in an air atmosphere, keep it at that temperature for 36 hours, then continue to heat it to 1500°C at a heating rate of 7°C / min, keep it at that temperature for 42 hours, and then cool it with the furnace.

[0120] Related performance test analysis:

[0121] 1. Using an X-ray fluorescence spectrometer (XRF) to test the impurity content in the tin oxide-based targets prepared in Examples 1 to 11;

[0122] It was found through testing that the contents of Ca, Fe, Si and Mn in the tin oxide-based targets prepared in Examples 1 to 11 were all lower than 20 ppm, and the total impurity content was lower than 100 ppm, indicating that the purity of the prepared target material can be improved by controlling the purity of the raw materials. The target material has high purity, which can reduce the impurities remaining in the film during target coating to form magnetic impurities and affect the optical and electrical properties of the coating, thereby having better photoelectric properties.

[0123] 2. The cross-sectional microstructure of the tin oxide-based target provided in Example 1 was tested using SEM. The test results are as follows: Figure 1As shown, from Figure 1 It can be seen that the tin oxide-based target has good grain uniformity and high density.

[0124] 3. The resistivity of the tin oxide-based targets prepared in Examples 1 to 11 and Comparative Examples 1 to 6 was tested by a four-probe method;

[0125] 4. The density of the low-resistance tin oxide-based targets prepared in Examples 1 to 11 and Comparative Examples 1 to 6 was tested using the Archimedes density test method.

[0126] The test results are shown in Table 1 below:

[0127] Table 1

[0128]

[0129]

[0130] As can be seen from Table 1, the resistivity of the tin oxide-based targets provided in Examples 1 to 11 is less than 50 mΩ·cm, and is significantly less than the resistivity of the tin oxide-based targets provided in Comparative Examples 1 and 3 to 5, and is slightly different from the resistivity of the tin oxide-based targets provided in Comparative Example 2. This is mainly due to the fact that the first dopant such as Sb is used in this embodiment. 2 O 5 , Nb 2 O 5 、MoO 3 , WO 3 Doped with a certain amount of Sb 5+ , Nb 5+ 、Bi 5+ or W 6+ These ions enter SnO 2 Substituting Sn in the lattice 4+ , which will introduce free electron carriers and increase the electron carrier concentration, thereby greatly reducing the resistivity of the tin oxide-based target material.

[0131] The density of the tin oxide-based targets provided in Examples 1 to 13 is greater than 6.5 g / cm 3 , and is significantly greater than the density of the tin oxide-based target provided in Comparative Examples 1 to 2, and is slightly different from the relative density of the tin oxide-based target provided in Comparative Example 3. This is mainly due to the fact that the second dopant such as ZnO, CuO, and Bi is used in the present embodiment. 2 O 3 , B 2 O 3 Equally doped Zn 2+ , Cu 2+ 、Bi 3+ , B 3 +These ions can promote SnO by generating oxygen vacancies or generating liquid phase. 2 densification sintering, thereby improving the target density.

[0132] The resistivity of the tin oxide-based target material provided in Example 1 is significantly lower than the resistivity of the tin oxide-based target material provided in Comparative Example 1, and the density of the tin oxide-based target material provided in Example 1 is significantly higher than the density of the tin oxide-based target material provided in Comparative Example 1, indicating that the embodiment of the present application first calcines the first dopant and the tin oxide powder to form a solid solution powder, and then sinters it with the second dopant, which makes it easier to form a uniform and dense tin oxide-based target material and reduce the resistivity.

[0133] The resistivity of the tin oxide-based target provided in Example 1 is significantly lower than that of the tin oxide-based target provided in Comparative Example 4, indicating that in the embodiment of the present application, cooling the calcined solid solution powder to a set temperature and keeping it warm for a period of time is more conducive to forming a solid solution powder with uniform structure.

[0134] The resistivity of the tin oxide-based target provided in Example 1 is significantly lower than that of the tin oxide-based target provided in Comparative Example 5, and the density of the tin oxide-based target provided in Example 1 is significantly higher than that of the tin oxide-based target provided in Comparative Example 5, indicating that the step-wise heating sintering adopted in the present application embodiment can make the particles more closely bonded, the target material structure more uniform and with higher density, and the target material resistance lower. In addition, during the cooling process, the introduction of argon-hydrogen mixed gas to form a reducing atmosphere can not only deoxygenate the target material, further reduce the resistivity of the target material, but also further promote the uniformity of the internal structure of the target material and increase the density.

[0135] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a low-resistance tin oxide-based target material, characterized in that: The following steps are involved: The first dopant, tin oxide powder, the first dispersant and the solvent are ball-milled and mixed under a grinding medium, and then dried to obtain a first mixed powder; calcining the first mixed powder to obtain a solid solution powder; The solid solution powder is mixed with a second dopant, a second dispersant, a binder and a solvent by ball milling, and then dried to obtain a second mixed powder; isostatically pressing the second mixed powder to form a green billet; The green blank is sintered to obtain a tin oxide-based target; The tin oxide-based target material includes SnO2, the first dopant and the second dopant, the first dopant includes at least one of Sb2O5, Nb2O5, Ta2O5, MoO3 and WO3; the second dopant includes at least one of ZnO, CuO, Bi2O3 and B2O3; The step of sintering the green blank comprises: placing the green blank in a sintering furnace, heating the green blank to 400-600°C at a heating rate of 5-10°C / min in an air atmosphere, keeping the temperature for 18-60 hours, heating the green blank to 600-800°C at a heating rate of 1-3°C / min, keeping the temperature for 4-6 hours, heating the green blank to 800-1400°C at a heating rate of 5-10°C / min, keeping the temperature for 12-18 hours, heating the green blank to 1400-1550°C at a heating rate of 1-3°C / min, keeping the temperature for 12-24 hours, cooling the green blank to 800-1200°C, introducing argon-hydrogen mixed gas, keeping the temperature for 2-6 hours, cooling the green blank to 700°C, stopping the introduction of gas, and cooling the green blank naturally.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the SnO2, the first dopant and the second dopant is (94-99.8): (0.1-3): (0.1-3).

3. The preparation method according to claim 1, characterized in that: The resistivity of the tin oxide-based target is ≤50 mΩ·cm, and the density is >6.5 g / cm 3 .

4. The preparation method according to claim 1, characterized in that: The mass ratio of the first dopant to the grinding medium is 1 / (1-3); And / or, the grinding media includes first zirconia beads, second zirconia beads, third zirconia beads and fourth zirconia beads in a mass ratio of 1:(2-4):(2-4):(4-8); wherein the particle sizes of the first zirconia beads, the second zirconia beads, the third zirconia beads and the fourth zirconia beads are 0.5-3 mm, 4-6 mm, 8-12 mm and 13-16 mm, respectively.

5. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the solid solution powder is 3 to 8 m 2 / g; the specific surface area of ​​the second mixed powder is 8~15m 2 / g.

6. The preparation method according to claim 1, characterized in that: The step of calcining the first mixed powder includes: heating the first mixed powder to 750-850° C., keeping the temperature for 4-12 hours, then cooling the first mixed powder to 450-550° C., keeping the temperature for 6-10 hours, and then cooling it with the furnace.

7. The preparation method according to claim 1, characterized in that: The addition amount of the first dispersant is 0.01-0.1% of the total mass of the first dopant and the tin oxide powder; And / or, the added amount of the second dispersant is 0.01-0.1% of the total mass of the solid solution powder and the second dopant.

8. The preparation method according to any one of claims 1 to 7, characterized in that The first dispersant is selected from ammonium polyacrylate, the second dispersant is selected from ammonium polycarboxylate, and the binder is selected from polyvinyl alcohol; And / or, the isostatic pressing pressure is 200-300 MPa.

Citation Information

Patent Citations

  • Transparent conductive film and method for manufacturing the transparent conductive film, and sputtering target used in the method

    CN101631892A

  • Tin oxide-based electrode composition

    CN102227781A

  • Tin Oxide Ceramic Sputtering Target And Method Of Producing It

    CN102811971A

  • Preparation method of trace element composite doping modified tin antimony oxide (ATO) ceramic target

    CN103739282A

  • Sn-Zn-O-BASED OXIDE SINTERED BODY AND METHOD FOR PRODUCING SAME

    CN108698937A